EU Social Inclusion Policies in Post-Socialist Countries Top-Down and Bottom-Up Perspectives on Implementation (Taylor & Francis, 2020)
This book explores experiences with inclusion policy implementation in seven different post-socialist EU countries. It focuses particularly on two groups of people in constant danger of social exclusion: People with Roma background and people with disabilities.
English
Keywords: Society & social sciences; Bulgaria; Czech Republic; Elena Baciu, Romania; EU Social Inclusion Policies; Hungary; Ingrid Fylling; Janne Paulsen Breimo; Poland; post-socialist countries; Serbia; Slovakia